Rationality, affect, and vote choice - Panagopoulos, Costas; Wang, Ching-Hsing (Frontiers in Political Science, 2025)
IntroductionAlthough both rational choice theory and emotion provide some explanatory power for individual voting behavior, few studies to date have simultaneously examined the effects of rationality (cognition) and emotion (affect) on vote choice. This study aims to fill that void and to explore the relative effects of rationality and emotion on individual political preferences.MethodsUsing data from the 2000–2016 American National Election Studies, we conducted statistical analyses to estimate the effects of the party differential and the emotion differential on individual voting decisions.ResultsFindings indicate that voters take competing parties’ policy positions as well as their emotional responses to competing candidates into consideration to make their voting decisions. That is, individual voting decisions are guided by both affect and rationality. Furthermore, affective orientations appear to exert a larger impact on vote choice compared to rational considerations.DiscussionThe results call greater attention to the affective underpinnings of voting decisions and suggest that models that exclude or otherwise minimize the influence of emotional considerations on vote choice are incomplete or underspecified.